Farmland valuation: a net present value approach using simulation - Westergard, Chris (Kansas State University, 2015)
As the single largest asset class on the agriculture sector’s balance sheet, real estate is clearly a significant component of America’s farming community’s well-being and key to production agriculture. Purchasing farmland requires a significant commitment of capital, and one of the chief considerations for producers when contemplating purchasing a property is the return they can expect to receive from their investment over the course of its productive life. The traditional Net Present Value approach to investment valuation is difficult to implement since estimating cash flows over the life of the property is extremely difficult due to uncertainty in yields and commodity prices. By using historical price, yield, and cost data, this thesis develops a net present value spreadsheet model that uses simulation to determine an expected cash flow per acre. This expected cash flow can then be used to determine the gross cash flow from a particular farm over the term of the investment. While not explicitly accounting for non-direct expenses in the model such as returns to management, the techniques discussed provide a solid foundation for a more thorough enterprise analysis and give the producer an estimate of cash flows independent of short-term management decisions.
Keywords: Land purchase; Net Present Value; Simulation; Montana Agriculture; Agriculture, General (0473); Economics, Agricultural (0503); Economics, Finance (0508)